Vibration of flexible robots: Dynamics and novel synthesis of unbounded trajectories - Debanik Roy (Annals of Robotics and Automation - Peertechz Publications, 2023)
Flexible Robotic Systems, by and large, are prone to inherent vibration that recreates itself in several modal frequencies. This in-situ vibration in flexible robots or in any such complaint robotic unit becomes tricky so far as the control system architecture is concerned. Thus, customization of the design and firmware of higher-order flexible robots is highly challenging due to its inherent parameters related to real-time vibration. Vibration in flexible robots has been investigated hitherto from the standpoint of frequency & amplitude tuple, sidetracking the important paradigm of looping of the trajectories. This work has added a technological niche in bringing out the intrinsic dynamics of this vibration from a mathematical perspective of trajectory formation so as to understand the mechanics of spiraling loops while a flexible/compliant robotic system is vibrating under natural conditions. The analytical modeling of the said in-situ vibration has been experimented with through an indigenous single-link flexible robot, fitted with a miniature gripper.